The Migration Dilemma of the Younger Generation from the Perspective of Wage Purchasing Power - Wypych, Nataniel; Zawolska, Zuzanna (Journal of Finance and Financial Law, 2023)
The purpose of the article. The aim of the article is to determine whether there is a need to differentiate between countries in terms of the amount of aid they provide for the return of their citizens, and in which of the European countries a person can save the most and build up wealth in the fastest way. Methodology. The study is based on historical data from 2016 to 2021 on average salaries, average cost of living, average price per square meter of housing in a country’s capital and the average price of a VW Golf IV car in 37 European countries. Results of the research. In the general view of the study presented below, the countries to which economic migration can bring the most benefits are Switzerland, Luxembourg, and Denmark. On the other hand, countries that may not meet economic needs include North Macedonia, Moldova, Montenegro, and Albania. One can save the fastest per square meter of housing in Belgium, Iceland, and Switzerland. The fastest way for people to save money for a car is available in Switzerland, Luxembourg, and Great Britain.